2020
DOI: 10.1155/2020/4324382
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Implant Utilization among Married Women of Childbearing Age in Chencha Town, Southern Ethiopia, 2017: A Case-Control Study

Abstract: Globally, 53% of women in reproductive age group use modern methods of contraception, with less than one percent of which using implants. In Ethiopia and other parts of sub-Saharan Africa, short-term contraceptive methods have been more utilized than long-acting methods like implants. Despite their effectiveness, implants have been underutilized due to various reasons. There is a dearth of stronger evidences on those factors in the country in general and the study area in particular. Therefore, this study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
5
7
0
Order By: Relevance
“…This finding is consistent with other studies. 3,4,12,[14][15][16] Most of the women (27.5%) had education up to SSC/HSC level and 22% had no formal education. This finding is similar to a study done by Mubarik et al 16 which reflects the education status of women in rural areas of Pakistan.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding is consistent with other studies. 3,4,12,[14][15][16] Most of the women (27.5%) had education up to SSC/HSC level and 22% had no formal education. This finding is similar to a study done by Mubarik et al 16 which reflects the education status of women in rural areas of Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…17 In this study, we found about 142 (71%) participants had adequate information or idea about subdermal implants which is in concordance with other studies. 3,4,18 But another study done by Mubarik et al in Pakistan showed that implant was used by a very little proportion of women which was only 21%. 16 This probably makes implant the least used contraceptive method in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations